2022
DOI: 10.1039/d2nj04194d
|View full text |Cite
|
Sign up to set email alerts
|

Facile and single step produced Ba:Sn-codoped PEDOT:PSS thin film electrode with improved optics and electrochemical properties for transparent and flexible supercapacitor applications

Abstract: Figure shows preparation and characterization steps of different ratio (0–3 mg ml−1) Ba:Sn-codoped PEDOT:PSS thin films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…This showed that the redox reaction was more easily carried out in the 1000th cycle as a function of the electrode/ electrolyte surface increase occurring on the electrode surface. 16,43,[74][75][76][77] Accordingly, the capacitive behavior of the system in the 1000th cycle increased significantly compared to the initial and 2000th cycle (Fig. 10c and Table II).…”
Section: Resultsmentioning
confidence: 93%
“…This showed that the redox reaction was more easily carried out in the 1000th cycle as a function of the electrode/ electrolyte surface increase occurring on the electrode surface. 16,43,[74][75][76][77] Accordingly, the capacitive behavior of the system in the 1000th cycle increased significantly compared to the initial and 2000th cycle (Fig. 10c and Table II).…”
Section: Resultsmentioning
confidence: 93%
“…EIS analysis was performed in the presence of 1 mM PC in 0.1 m PBS (pH 7.0). The EIS analysis was perofrmed at the open circuit potential and the frequency range of 1-10000 Hz, the amplitude of 0.005 V. 34,45 The curves were fitted using an equivalent simple circuit model. The error rates in the fit values were below 5%.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of ChCl loaded NPs, the main peaks of choline chloride were absent and the ChCl loaded NPs exhibited the same characteristics as the free NPs, indicating that the ChCl loaded NPs were in a highly amorphous state and successfully encapsulated to NPs. There were no new sharp and broad peaks observed or no significant shift in the peaks and also the absence of a transition from amorphous to a crystalline character indicated that there was no ChCl on the surface after encapsulation (Yağci, Arvas, & Yazar, 2022). The in-vitro release profiles of the C1-C4 NPs were investigated to demonstrate ChCl's ability to reduce or increase drug release.…”
Section: Production and Characterization Of The Nanoparticlesmentioning
confidence: 99%